2017
DOI: 10.1080/14786419.2017.1295240
|View full text |Cite
|
Sign up to set email alerts
|

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09

Abstract: An actinomycete strain 200-09, isolated from a soil sample collected from the coast of Hawaii, USA, was identified as Streptomyces antibioticus on the basis of its morphological, physiological and biochemical characteristics as well as 16S rDNA analysis. A new antimycin-type antibiotic, kitamycin C (1), together with kitamycin A (2), kitamycin B (3), urauchmycin B (4), deisovaleryblastomycin (5) was isolated from a cultured broth of strain 200-09. The structure of the new compound was determined by spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…S. antibioticus was originally isolated from soil and is well known for its potential to produce several bioactive compounds, including several antibiotics. There are strains of S. antibioticus isolated form marine environment which may explain the halophilic properties of the Streptomyces S3 isolate (Sharma et al, 2019;Waksman and Woodruff, 1941;Wang et al, 2017;Xu et al, 2011). Automated genome blast-based phylogeny retrieved from NCBI indicated that soil environmental isolate Streptomyces sp.…”
Section: Genome Analysismentioning
confidence: 99%
“…S. antibioticus was originally isolated from soil and is well known for its potential to produce several bioactive compounds, including several antibiotics. There are strains of S. antibioticus isolated form marine environment which may explain the halophilic properties of the Streptomyces S3 isolate (Sharma et al, 2019;Waksman and Woodruff, 1941;Wang et al, 2017;Xu et al, 2011). Automated genome blast-based phylogeny retrieved from NCBI indicated that soil environmental isolate Streptomyces sp.…”
Section: Genome Analysismentioning
confidence: 99%
“…They are characterized by a nine-membered dilactone skeleton substituted with one alkyl (C7), one acyloxy (C8), two methyl moieties (C4 and C9), and a 3-formamidosalicylic acid linked to C3 by an amide connection . Although the most abundant members of this family are the ones with a nine-membered core, antimycin-type macrocyclic compounds with 12-, 15-, and 18-membered rings have also been reported. Antimycins exhibit a broad spectrum of biological properties, including antifungal, antiviral, , or mitochondrial electron transport inhibitors. The first antimycin reported possessing a pyridyl group was the antibiotic UK-2A, isolated from an acetone extract of Streptomyces sp. 517-02 in 1996. , Biological and structure–activity relationships of UK-2A have been studied comparing its activity with those of other antimycins scaffolds like spleniocins. , The antifungal activity of these compounds has been described to be triggered by the inhibition of electron transport at mitochondrial complex III .…”
Section: Introductionmentioning
confidence: 99%
“…A new antimycintype antibiotic, kitamycin C was recently isolated from a culture broth of Streptomyces antibioticus strain 200-09. The compound exhibited strong antifungal activities against Candida albicans [25]. Two new antimycin A analogues were isolated from a spent broth of a marine-derived Streptomyces lusitanus, and these compounds also showed strong biological activity against Staphylococcus aureus and Loktanella hongkongensis [26].…”
Section: Introductionmentioning
confidence: 99%